Perancangan Prototipe Alat Pengurai Asap Rokok Menggunakan Electrostatic Precipitator - Emilia Roza; Yogi Sugiharto; Rosalina Rosalina (Jetri : Jurnal Ilmiah Teknik Elektro, 2022)
One of the causes of poor air quality is the high number of smokers in Indonesia. A smoking room in public places equipped with cigarette smoke decomposers is important. The purpose of this study was to determine the ratio of the percentage decomposition of smoke levels in tests using and without using ESP. The tool is made to be able to monitor air quality based on ISPU using an MQ2 sensor with an output in the form of a blower that functions to direct smoke out of the room, then the smoke will be processed into clean air using an electrostatic precipitator (ESP). The simulation results show that by using ESP (electrostatic precipitator) the smoke content can be decomposed up to 92.867%, while without ESP, it is not more than 5% so that it can pollute the environment around the smoking room. Salah satu penyebab buruknya kualitas udara adalah tingginya jumlah perokok di Indonesia. Adanya smoking room di tempat umum yang dilengkapi dengan alat pengurai asap rokok menjadi penting. Adapun tujuan dari penelitian ini adalah menentukan perbandingan persentase penguraian kadar asap pada pengujian menggunakan dan tanpa menggunakan ESP. Alat dibuat agar dapat memantau kualitas udara bersadarkan ISPU menggunakan sensor MQ2 dengan output berupa blower yang berfungsi mengarahkan asap keluar ruangan,  selanjutnya asap akan diolah menjadi udara bersih menggunakan electrostatic precipitator (ESP). Hasil simulasi menunjukkan bahwa dengan menggunakan ESP (electrostatic precipitator) kadar asap dapat terurai hingga 92,867%, sedangkan tanpa ESP,  tidak lebih dari 5% sehingga dapat mencemari lingkungan sekitar smoking room.